Linking folklore to agricultural sustainability accounting in Bangladesh - Khan, Mahmood; Marinova, Dora; Todorov, Vladislav (2021)
The Bangladeshi folklore cultural heritage embraces myriad proverbs, adages, sayings, folktales, and folksongs, including the songs of the Baul mystic minstrels. Many are linked to various aspects of agriculture – from tilling to harvest, storage of yields, and consumption. The paper draws on this folklore to develop the concept of traditional sustainability accounting in agriculture. Although without formal quantification, these proverbs and songs guide agricultural practices in rural Bangladesh maintaining a socio-economic system that promotes sustainable activities, counteracts the damage caused by the 1970 Green Revolution, and encourage sustainability accounting. In recent years, Bangladesh has achieved many of the Millennium Development Goals but has also witnessed environmental deterioration. An agro-ecological management informed by folklore and traditional wisdom has the potential to transform the country's progress along the lines of the UN Sustainable Development Goals.